If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -16 = 4a + 2a Combine like terms: 4a + 2a = 6a -16 = 6a Solving -16 = 6a Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '-6a' to each side of the equation. -16 + -6a = 6a + -6a Combine like terms: 6a + -6a = 0 -16 + -6a = 0 Add '16' to each side of the equation. -16 + 16 + -6a = 0 + 16 Combine like terms: -16 + 16 = 0 0 + -6a = 0 + 16 -6a = 0 + 16 Combine like terms: 0 + 16 = 16 -6a = 16 Divide each side by '-6'. a = -2.666666667 Simplifying a = -2.666666667
| 16.7d+66.7=25d+-.5 | | .666(5)= | | 3.5s-7.3=-7.3+2.6s | | (2x-11)/3=4+x | | x+7/2=7 | | -8x-16=-8(2x-6) | | -16=14a+2a | | 16n+1=80 | | 5-(3-f)-5=6(3-f) | | (5x/2)=3x+5 | | (2x-11)/3=4/3+x | | 22/11x9-3^2 | | 5y=-6(0)-30 | | (x+2)/(x-3)=2 | | v=x(18-2x)(9-2x) | | 4x=-2(2x+4) | | x^2+8x+12y+4=0 | | (7xy)-(3xy)= | | 6m+7m=0 | | x(3x^2-5x-2)=0 | | 8+x=-31 | | 6(v+3)-2v=2(2v+3)-14 | | -3=-1/3h-10 | | 2/3x-12 | | 3-(x-4)=48 | | 18=x+3+2x | | 42/18 | | 15-3k=5(k-5)-3k | | (2/3)x-(1/6)=(2/7) | | d=85t+340 | | 3(3*x+4*y+5)+2(2*x-4*y-3)=z | | 2x=4x+18 |